Adaptive laboratory evolution of cadmium tolerance in Synechocystis sp. PCC 6803 - Chunxiao Xu; Tao Sun; Shubin Li; Lei Chen; Weiwen Zhang (Biotechnology for Biofuels, 2018)
Abstract Background Cadmium has been a significant threat to environment and human health due to its high toxicity and wide application in fossil-fuel burning and battery industry. Cyanobacteria are one of the most dominant prokaryotes, and the previous studies suggested that they could be valuable in removing Cd2+ from waste water. However, currently, the tolerance to cadmium is very low in cyanobacteria. To further engineer cyanobacteria for the environmental application, it is thus necessary to determine the mechanism that they respond to high concentration of cadmium. Results In this study, a robust strain of Synechocystis PCC 6803 (named ALE-9.0) tolerant to CdSO4 with a concentration up to 9.0 µM was successfully isolated via adaptive laboratory evolution over 802-day continuous passages under cadmium stress. Whole-genome re-sequencing was then performed and nine mutations were identified for the evolved strain compared to the wild-type strain. Among these mutations, a large fragment deletion in slr0454 encoding a cation or drug efflux system protein was found to contribute directly to the resistance to Cd2+ stress. In addition, five other mutations were also demonstrated related to the improved Cd2+ tolerance in ALE-9.0. Moreover, the evolved ALE-9.0 strain was found to obtain cross tolerance to some other heavy metals like zinc and cobalt as well as higher resistance to high light. Conclusions The work here identified six genes and their mutations related to Cd2+ tolerance in Synechocystis PCC 6803, and demonstrated the feasibility of adaptive laboratory evolution in tolerance modifications. This work also provided valuable information regarding the cadmium tolerance mechanism in Synechocystis PCC 6803, and useful insights for cyanobacterial robustness and tolerance engineering.